Political Development in Emerging Nations : Is There Still a Third World? - Wiarda, Howard J (Thomson Wadsworth, 2004)
This book reviews what has been learned about national development in the Third World in the last 50 years: what works and what doesn't work. Wiarda surveys all the major themes and theories in the field: developmentalism, dependency theory, democratization, globalization, and neo-liberalism. This book is the most up-to-date survey of the entire field of development studies, drawing on Professor Wiarda's academic research and his extensive Washington policy experience. As a new addition to the Wadsworth series, NEW HORIZONS IN COMPARATIVE POLITICS, this book can also be coupled with other books in the series to provide tailored coverage of specifically chosen countries and topics